2014
DOI: 10.1093/rheumatology/keu228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of relapse predictors in IgG4-related disease using multivariate analysis of clinical data at the first visit and initial treatment

Abstract: Follow-up is important in cases with recognized risk factors for relapse, including male sex and younger onset in cases without organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 10 publications
0
39
4
1
Order By: Relevance
“…We have previously shown that serum IgG4 level increases with the number of inflamed regions. 21 It 24 In the present study, no correlation was observed between serum IgG4 level and relapse ( Figure S2). One possible reason was the significant differences of serum IgG4 levels between the involved organs.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We have previously shown that serum IgG4 level increases with the number of inflamed regions. 21 It 24 In the present study, no correlation was observed between serum IgG4 level and relapse ( Figure S2). One possible reason was the significant differences of serum IgG4 levels between the involved organs.…”
Section: Discussioncontrasting
confidence: 62%
“…It is unclear whether there is a relationship between serum IgG4 levels and relapse. Although some studies have shown that elevated serum IgG4 levels is a predictor for relapse, others have produced opposite results . In the present study, no correlation was observed between serum IgG4 level and relapse (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified the relapse predictors in IgG4-RD using multivariate analysis of clinical data at the first visit and initial treatment; they were male sex and younger onset in cases without organ involvement at diagnosis, and low levels of serum IgG4 in cases with organ dysfunction at diagnosis. Autoimmune pancreatitis and low steroid dose at initial treatment also tended to be associated with recurrence [13]. In the present analysis, it was difficult to interpret the results because sex and organ involvement were excluded, but Cluster 3 had features similar to those described above, younger onset, and low levels of serum IgG4.…”
Section: Discussionmentioning
confidence: 61%
“…Yamamoto et al analyzed risk factors for the relapse for patients with IgG4-RD and reported that low steroid dose at initial treatment tended to be associated with recurrence. 25 They also suggested that complication with autoimmune pancreatitis and the use of low-dose glucocorticoid at initial induction therapy tended to be associated with relapse in cases with organ involvement. In our study, although the remission rate was similar in high and medium dose groups in the previous 3 months, a higher relapse rate was observed at week 24 in the medium dose group.…”
Section: -13mentioning
confidence: 99%